Valproic Acid After Neurosurgery Induces Elevated Risk of Liver Injury: A Prospective Nested Case-Control Study. Issue 8 (August 2022) - Guo, Jinlin; Ma, Jiuhong; Wang, Shan; Li, Xingang; Ji, Hongming; Li, Yuanping; Peng, Fangchen; Sun, Yiqi
Background: Valproic acid (VPA) has been widely used to prevent epileptic seizures after neurosurgery in China. We have found that the incidence of liver injury (LI) in patients using VPA after neurosurgery is higher than that in other patients. Objective: The objective of this study was to investigate the risk factors of LI in patients using VPA after neurosurgery. Methods: A nested case-control study was conducted in patients using VPA after neurosurgery between September 2019 and March 2021. Cases of LI were matched to controls by age and body mass index (BMI). Conditional logistic regression was used to estimate matched odds ratios representing the odds of LI. A receiver operating characteristic curve was used to analyze the optimal cutoff condition. Results: A total of 248 people (62 LI and 186 control) were enrolled. Among patients with vs without LI, the matched odds ratio for trough concentration of VPA was significant (matched odds ratio [OR], 1.09; 95% confidence interval [CI]: 1.01-1.19). The course of treatment (OR: 1.17, 95% CI: 1.02-1.33), Glasgow score (OR: 0.26, 95% CI: 0.10-0.67), gene polymorphisms of CYP2C19 (OR: 2.09, 95% CI: 1.03-146.93), and UGT1A6 (OR: 34.61, 95% CI: 1.19-1003.23) were all related to the outcome. The optimal cutoff of the course of treatment was 10 days, while the trough concentration of VPA was determined to be 66.16 mg/L. Conclusion: Length of treatment, VPA trough concentration, and Glasgow score were associated with LI in patients after neurosurgery. A gene test may be necessary for people who are prescribed VPA for a long time.